The Influence of Doxorubicin on Testicular Histology and Sperm Parameters in Male Wistar Rats - Noor Hassoon Al-Qaraghuli (Genius Journals, 2023)
Chemotherapy plays a vital role in cancer treatment, but its impact on normal tissues and organs, including male reproductive function, is a significant concern. This study aimed to assess the influence of Doxorubicin, a commonly used chemotherapeutic agent, on testicular histology and sperm parameters in male Wistar albino rats. Thirty healthy adult rats were randomly assigned to a control group and two experimental groups receiving doses of Doxorubicin. Testicular histology was evaluated using hematoxylin and eosin staining, while sperm parameters, including general motility, progressive motility, viability, acrosomal integrity, morphology integrity, and concentration, were assessed. The results demonstrated remarkable histopathological changes in the testicular tissue of the experimental groups compared to the control group. Doxorubicin administration significantly reduced sperm motility, viability, acrosomal integrity, morphology integrity, and concentration. The findings of this study align with previous research, further highlighting the harmful effects of Doxorubicin on testicular function and sperm quality.
Keywords: Doxorubicin; Testicular Histology; Sperm Parameters